Domestic Minor Sex Trafficking: A Case Series of Male Pediatric Patients. Issue 23 (December 2021) - Moore, Jessica; Fitzgerald, Meagan; Owens, Timothy; Slingsby, Brett; Barron, Christine; Goldberg, Amy
Domestic minor sex trafficking (DMST) is the commercial sexual exploitation of children (<18 years old) who are U.S. citizens or lawful permanent residents, victimized within U.S. borders. There is limited knowledge and research in regard to male involvement in DMST outside the context of homelessness and runaway youth. To our knowledge, no research specifically examines at-risk or involved male youth from a larger dataset of youth who present to a child abuse outpatient medical clinic. The objective of the present case series was to describe the demographic, psychosocial, medical, and psychiatric characteristics of natal male participants (who did not identify as transgender) suspected of DMST involvement. Six medical records of male patients under the age of 18 who were referred to a child protection clinic for concern of DMST involvement between 8/1/13 and 12/31/18 were retrospectively reviewed. Our case series demonstrates that male participants present for concern of sex trafficking and have complex behavioral, medical, and psychiatric concerns similar to what has been identified in research focused on female victims. Therefore, testing (e.g., sexually transmitted infection (STI)/HIV testing, urine toxicology screening), DMST screening, and interventions (e.g., STI prophylaxis, referrals to mental health counselors) should be completed in male patients.